Application of Talking Stick-Based Learning Media to Improve Students' Critical Thinking - Nabila Veronika; Muhammad Sadri; Zulham Siregar (Edunesia: Jurnal Ilmiah Pendidikan, 2023)
The reason for this study is learners' low critical thinking ability on the material "economic activity". This study aims to describe the results of the application of Talking Stick-based learning media to students' critical thinking skills on the material of economic activities carried out in class VII I of Al Maksum Stabat Private Junior High School. This research method uses a qualitative method with a descriptive approach. The data collection techniques used are interviews and documentation. The research acts as a data collection instrument. According to Miles and Huberman, the data analysis techniques used are data reduction, data presentation (data display), and conclusion drawing/verification. The research subjects used are students of class VII I of the 2022/2023 school year. The number of students is 25 people. The results of this study showed learners' critical thinking ability on the material of economic activity. Seven participants in Students were able to answer when they got their turn in the talking stick game, while 2 students were still reluctant to answer questions. Researchers use questionnaires to discover the development and influence of the application of Talking Stick learning media.